A cesium-based metal halide composite light-conversion packaging film and a preparation method thereof

By using a cesium-based metal halide composite converting light encapsulation film in the packaging film of solar cells, ultraviolet light is absorbed and converted into visible light, the damage problem of ultraviolet light on solar cells is solved, and the power generation efficiency and service life are improved.

CN119081586BActive Publication Date: 2025-03-25SUZHOU HONDOL NEW MATERIAL LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411556054.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-03-25
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively protect solar cells from ultraviolet light, resulting in reduced power generation efficiency and shortened service life.

Method used

A cesium-based metal halide composite conversion-optical encapsulation film is used to prepare cesium-based metal halide by hydrothermal method, and combined with polymer materials, white oil and PBAT dispersant to form a film that can absorb ultraviolet light and convert it into visible light.

Benefits of technology

It improves the absorption of visible light by solar cells, enhances the photoelectric conversion efficiency, extends the service life of the module, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119081586B_ABST
    Figure CN119081586B_ABST
Patent Text Reader

Abstract

The present invention provides a cesium-based metal halide composite light-converting packaging film and a preparation method thereof, and relates to the technical field of film materials. The preparation method of the light-converting packaging film comprises the steps of: S1, preparing cesium-based metal halide by hydrothermal method: dissolving cadmium chloride and chloride of metal X in hydrochloric acid solution to obtain mixture A; mixing mixture A with cesium chloride for heat preservation to obtain Cs(Cd-X)Cl3; the metal X is selected from at least one of Mn, Sb, Eu, and Fe; the doping ratio of metal X is 0.1-15%; S2, mixing Cs(Cd-X)Cl3, polymer material, white oil and PBAT dispersant to prepare the light-converting packaging film. The obtained cesium-based metal halide of the present invention can absorb ultraviolet light and convert it into visible light, improve power generation efficiency, and reduce the damage of ultraviolet light to solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesive film materials, and in particular relates to a cesium-based metal halide composite light-conversion packaging adhesive film and a preparation method thereof. Background Art

[0002] The solar spectrum refers to the continuous spectrum of different wavelengths radiated by the sun. According to the different wavelengths, the solar spectrum can be divided into three parts: ultraviolet light, visible light and infrared light. Visible light can be absorbed by the main body of the solar cell, and the excited carriers can easily enter the external circuit. The power generation efficiency of solar cells in the medium wavelength range is higher. Ultraviolet light and infrared light are invisible light; the photon energy of infrared light is too low to excite carriers, and solar cells do not respond to infrared light.

[0003] The wavelength of ultraviolet light is relatively short, and the solar cell material has a weak ability to absorb ultraviolet light, so the solar cell has a low utilization rate of the ultraviolet band of sunlight. In addition, ultraviolet light can also cause the encapsulation film of the solar cell to age, reducing its transmittance to sunlight, thereby further reducing the power generation efficiency of the solar cell. And for heterojunction solar cells and perovskite solar cells, ultraviolet light can also destroy the light-absorbing material, reducing the service life of the photovoltaic module.

[0004] Therefore, protecting solar cells from the effects of ultraviolet light is very important for extending the service life of solar cells and improving power generation efficiency. Based on this, researchers have made a series of technical improvements to photovoltaic materials such as encapsulation films.

[0005] Chinese invention patent CN117887377A discloses a high-reflection packaging film for a busbar-free battery assembly, a preparation method thereof, and a photovoltaic assembly. The high-reflection packaging film for a busbar-free battery assembly comprises a bearing layer, a light conversion layer, and an infrared reflection layer; the bearing layer comprises 50-80 parts of TPO resin, 20-50 parts of POE resin, and Eu 3+ 0.05-0.5 parts of modified organic light-converting powder and additives; the light-converting layer includes 100 parts of EVA resin, Eu 3+ Modified organic light-converting powder 0.05-0.5 parts and additives; infrared reflection layer includes POE resin 100 parts, Eu 3+ 0.05-0.5 parts of modified organic light-converting powder, 0.5-10 parts of rare earth manganese oxide and auxiliary agent. 3+ The modified organic photoconversion powder converts the transmitted ultraviolet light into red light; the photoconversion layer in the middle can convert part of the ultraviolet light passing through the photoconversion layer into red light, which is then reflected onto the battery cell through the infrared reflection layer, achieving a certain degree of power gain.

[0006] Chinese invention patent CN116970346A discloses a method for preparing a perovskite quantum dot light-converting adhesive film, comprising the following steps: forming a perovskite quantum dot light-converting adhesive film by extrusion molding a mixture containing a perovskite precursor material and an adhesive film polymer material; the perovskite precursor material comprises a cesium source material, a lead source material and a halogen source material; the halogen source material contains chlorine and / or bromine. The invention obtains an infrared light-converting film with a quantum tailoring effect by doping with rare earth elements.

[0007] In addition, researchers also use high-transmittance glass and anti-reflection glass to increase the penetration of light energy and improve the efficiency of light energy utilization. Polypropylene with high UV transmittance is used to increase short-circuit current and power generation efficiency, thereby improving the performance of photovoltaic modules. However, the above technologies greatly increase production costs, the film stability is average, and the use of lead source materials can also lead to lead pollution and lead poisoning.

[0008] Based on this, the present invention provides a cesium-based metal halide composite light-conversion packaging film and its preparation method and application, which absorbs ultraviolet light and converts it into visible light, enhances the absorption of visible light by photovoltaic modules, improves the photoelectric conversion efficiency, reduces the damage of ultraviolet light to modules, and prolongs the service life. Summary of the invention

[0009] The present invention aims at the problems existing in the prior art and provides a cesium-based metal halide composite light-conversion packaging adhesive film and a preparation method thereof. The cesium-based metal halide of the present invention can absorb ultraviolet light and convert it into visible light, thereby increasing the energy of visible light, so that solar cells can utilize more energy when receiving light energy, thereby improving power generation efficiency; the light-conversion packaging adhesive film of the present invention can reduce the damage of ultraviolet light to solar cells and extend the service life of components.

[0010] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0011] First, the present invention provides a method for preparing a cesium-based metal halide composite light-converting packaging film, comprising the steps of:

[0012] S1. Prepare cesium-based metal halide by hydrothermal method: dissolve cadmium chloride (CdCl2) and chloride of metal X in hydrochloric acid solution to obtain mixture A; mix mixture A with cesium chloride (CsCl) and keep warm to obtain Cs(Cd-X)Cl3 (cesium-based metal halide);

[0013] The metal X is selected from at least one of Mn, Sb, Eu, and Fe; the doping ratio of the metal X is 0.1-15%;

[0014] S2. Preparation of light-converting packaging film: Cs(Cd-X)Cl3 is mixed with polymer material, white oil and PBAT dispersant, and processed by a granulating extruder and a tablet press to obtain a light-converting packaging film with a thickness of 50-110 μm.

[0015] The cesium-based metal halide in step S1 of the present invention comprises cesium-based halide CsCdCl3 and metal X.

[0016] Preferably, in step S1, the doping ratio of the metal X is 1-5%.

[0017] Further preferably, in step S1, the doping ratio of the metal X is 2%.

[0018] In the present invention, the doping ratio of the metal X refers to the molar ratio of the metal X to (X+Cd); the doping ratio includes any range, real number and endpoint value within the numerical range, for example but not limited to: 0.1-2%, 2-5%, 1-5%, 5-10%, 2-10%, 10-15%, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%.

[0019] Preferably, in step S1, the mass concentration of the hydrochloric acid solution is 30-40wt%; further preferably, the mass concentration of the hydrochloric acid solution is 36wt%.

[0020] Preferably, in step S1, the mass ratio of cadmium chloride to cesium chloride is 1:7-10; further preferably, the mass ratio of cadmium chloride to cesium chloride is 1:8-9; further preferably, the mass ratio of cadmium chloride to cesium chloride is 1:8.8.

[0021] Preferably, in step S1, the mass volume ratio of cesium chloride to hydrochloric acid solution is 2.5-4:70 g / mL.

[0022] Further preferably, in step S1, the mass volume ratio of the cesium chloride to the hydrochloric acid solution is 3.367:70 g / mL.

[0023] Preferably, in step S1, the mixing and heat preservation is: heat preservation at 150-170°C for 8-16 hours, then cool to room temperature at a rate of 0.3-1°C / min, and store at room temperature for 36-54 hours.

[0024] Further preferably, in step S1, the mixing and heat preservation is: heat preservation at 160°C for 12 hours, then cool to room temperature at a rate of 0.5°C / min, and store at room temperature for 48 hours.

[0025] Preferably, step S1 further comprises washing and drying steps after mixing and heat preservation.

[0026] Further preferably, the washing and drying steps are specifically as follows: washing the white precipitate with water and ethanol in sequence, and then drying it at 50-70° C. for 12 hours to obtain a cesium-based metal halide.

[0027] Preferably, in step S1, the metal X is Mn.

[0028] Preferably, in step S2, the polymer material is selected from at least one of polypropylene, polycarbonate, polymethyl methacrylate, polyvinylidene fluoride, ethylene-vinyl alcohol copolymer, acrylonitrile-butadiene-styrene copolymer, polyvinylidene chloride, polyethylene terephthalate, and polyethylene terephthalate.

[0029] Further preferably, the polymer material is polypropylene.

[0030] Preferably, in step S2, the white oil is mineral oil.

[0031] Preferably, in step S2, the PBAT dispersant is polybutylene terephthalate-adipate.

[0032] Preferably, in step S2, the parameters of the granulation extruder are: 210-240°C for the middle module and 180-200°C for the two end modules.

[0033] Further preferably, in step S2, the parameters of the granulation extruder are: 220°C for the middle module and 190°C for the two end modules.

[0034] Preferably, in step S2, the operating temperature of the tablet press is 180-240°C; further preferably, the operating temperature of the tablet press is 220°C.

[0035] Preferably, in step S2, the extrusion thickness of the tablet press is 50-60 μm or 100-110 μm; further preferably, in step S2, the extrusion thickness of the tablet press is 50 μm.

[0036] Preferably, in step S2, the mass ratio of Cs(Cd-X)Cl3 to the polymer material is 1-3:50-150; further preferably, the mass ratio of Cs(Cd-X)Cl3 to the polymer material is 1-3:100; further preferably, the mass ratio of Cs(Cd-X)Cl3 to the polymer material is 2:100.

[0037] Preferably, in step S2, the mass ratio of Cs(Cd-X)Cl3, polymer material and PBAT dispersant is 1-3:50-150:0.5-2; the mass volume ratio of Cs(Cd-X)Cl3 to white oil is 20:3-8 g / mL.

[0038] Further preferably, the mass ratio of the Cs(Cd-X)Cl3, polymer material and PBAT dispersant is 2:100:1; the mass volume ratio of Cs(Cd-X)Cl3 to white oil is 20:5 g / mL.

[0039] Then, the present invention provides a light-converting packaging film, which is prepared by the above preparation method and includes components: cesium-based metal halide (Cs(Cd-X)Cl3), polymer material, white oil and PBAT dispersant; the cesium-based halide is CsCdCl3.

[0040] Preferably, the mass ratio of the Cs(Cd-X)Cl3, polymer material and PBAT dispersant is 1-3:50-150:0.5-2; the mass volume ratio of Cs(Cd-X)Cl3 to white oil is 20:3-8 g / mL.

[0041] Further preferably, the mass ratio of the Cs(Cd-X)Cl3, polymer material and PBAT dispersant is 2:100:1; the mass volume ratio of Cs(Cd-X)Cl3 to white oil is 20:5 g / mL.

[0042] Preferably, the metal X is selected from at least one of Mn, Sb, Eu and Fe.

[0043] Preferably, the polymer material is selected from at least one of polypropylene, polycarbonate, polymethyl methacrylate, polyvinylidene fluoride, ethylene-vinyl alcohol copolymer, acrylonitrile-butadiene-styrene copolymer, polyvinylidene chloride, polyethylene terephthalate, and polyethylene terephthalate.

[0044] Furthermore, the present invention provides a cesium-based metal halide prepared by the above preparation method, comprising CsCdCl3 and metal X, wherein the metal X is selected from at least one of Mn, Sb, Eu, and Fe.

[0045] Finally, the present invention provides the use of the above-mentioned cesium-based metal halide in the preparation of a light-converting packaging film.

[0046] Compared with the prior art, the present invention has the following beneficial effects:

[0047] 1. The present invention provides a cesium-based metal halide, wherein the metal X is selected from at least one of Mn, Sb, Eu, and Fe; the cesium-based metal halide can absorb ultraviolet light and convert it into visible light, thereby increasing the energy of visible light, so that the solar cell can utilize more energy when receiving light energy, thereby improving the power generation efficiency.

[0048] 2. The light-converting encapsulating film of the present invention can reduce the damage of ultraviolet light to solar cells and extend the service life of the components; the preparation process of the present invention is simple and environmentally friendly, compatible with existing photovoltaic production processes, and brings greater economic benefits in applications in the photovoltaic field. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 It is the emission spectrum of the CsCdCl3 sample of comparative example 1 of the present invention.

[0050] Figure 2 This is the emission spectrum of the CsCdCl3:2%Mn sample in Example 1.

[0051] Figure 3 It is the ultraviolet absorption spectra of Example 1 CsCdCl3:2%Mn and Comparative Example 1 CsCdCl3.

[0052] Figure 4 It is the X-ray diffraction pattern of Example 1 CsCdCl3:2%Mn and Comparative Example 1 CsCdCl3.

[0053] Figure 5 1 is the emission spectrum of the light-converting packaging film prepared in Example 1.

[0054] Figure 6 This is the ultraviolet absorption spectrum of the light-converting packaging film prepared in Example 1.

[0055] Figure 7 This is a comparison chart of the fluorescence quantum yield test of the light-converting packaging film prepared in Example 1.

[0056] Figure 8 This is a comparison chart of the water stability test of the light conversion packaging film prepared in Example 1; Figure 8 The lines from top to bottom at 604 nm are the fluorescence intensity data of the 1st day, the 5th day, the 10th day, the 15th day, the 20th day, and the 30th day, respectively.

[0057] Fig. 9 This is a surface scanning electron microscope test image of the light-converting packaging film prepared in Example 1.

[0058] Fig.10 This is a test diagram of surface element distribution of the light-converting packaging film prepared in Example 1.

[0059] Fig.11 This is a test chart of the surface roughness of the light-converting packaging film prepared in Example 1.

[0060] Fig.12 These are the actual pictures of the light-converting packaging film prepared in Example 1 under a fluorescent lamp and under 300nm ultraviolet light irradiation. DETAILED DESCRIPTION

[0061] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is merely an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the present invention based on the disclosed content, which should also fall within the scope of the present invention.

[0062] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those generally understood by those of ordinary skill in the art to which the present invention belongs.

[0063] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.

[0064] In the following embodiments, the polypropylene is purchased from Adamas with a product number of 013629479; the white oil is purchased from Adamas with a product number of 01156172 and a CAS number of 8042-47-5; and the PBAT dispersant is polybutylene terephthalate-adipate, purchased from Adamas with a product number of 013658669 and a CAS number of 55231-08-8.

[0065] The raw materials in the following embodiments and the raw materials products from different manufacturers have no significant influence on the effects.

[0066] Example 1

[0067] A method for preparing a cesium-based Mn halide composite light-converting packaging film, comprising the following steps:

[0068] S1. Prepare cesium-based metal halide doped with 2% Mn (CsCdCl3:2%Mn) by hydrothermal method:

[0069] According to the stoichiometric ratio of 2% Mn doping, MnCl2·4H2O (4.04 mg) and CdCl2 (0.3797 g) were weighed and added into a 100 mL polytetrafluoroethylene reactor; 70 mL of HCl (36 wt%) solution was added into the polytetrafluoroethylene reactor and shaken vigorously for 2 min until the powder was completely dissolved;

[0070] Weigh CsCl (3.367 g) and add it to the above polytetrafluoroethylene reactor. A white precipitate is immediately generated. Shake vigorously for 2 min. Then keep the temperature at 160°C for 12 h, then cool to room temperature at a rate of 0.5°C / min and keep the temperature for 48 h.

[0071] After the reaction is completed, the white precipitate sample is washed with deionized water and ethanol in turn; the obtained sample is dried at 60°C for 12 hours to obtain a cesium-based metal halide doped with 2% Mn (CsCdCl3:2%Mn), which can convert ultraviolet light into orange-red light.

[0072] S2. Preparation of light-converting packaging film:

[0073] Heat the pelletizing extruder to 220°C in the middle module and 190°C at both end modules, add polypropylene pellets for flushing until the extruded strips are transparent;

[0074] Take 20g CsCdCl3:2%Mn, grind it to 10-30μm, add 1kg polypropylene particles, 5mL white oil, and 10g PBAT dispersant in sequence, stir thoroughly, add it to the granulation extruder, and cut the extruded strips into particles; add the above particles to a tablet press at 220℃ and extrude it. The extrusion thickness of the tablet press is adjusted to 50μm to obtain a light-converting encapsulation film.

[0075] Example 2

[0076] The difference from Example 1 is that the doping ratio of Mn in step S1 is different, and the doping ratio of this embodiment is 5%.

[0077] The rest is the same as in Example 1 to obtain a light-converting packaging film.

[0078] Example 3

[0079] The difference from Example 1 is that the doping ratio of Mn in step S1 is different, and the doping ratio of this embodiment is 1%.

[0080] The rest is the same as in Example 1 to obtain a light-converting packaging film.

[0081] Example 4

[0082] Example 4-1

[0083] The difference from Example 1 is that the metal X in step S1 is Sb, and MnCl2·4H2O (0.1878 g) is replaced by antimony trichloride with the same doping ratio (2%). The rest is the same as Example 1 to obtain a light-converting packaging film.

[0084] Example 4-2

[0085] The difference from Example 1 is that the metal X in step S1 is Eu, and MnCl2·4H2O is replaced by europium (III) chloride hexahydrate with the same doping ratio (2%). The rest is the same as Example 1 to obtain a light conversion packaging film.

[0086] Example 4-3

[0087] The difference from Example 1 is that the metal X in step S1 is Fe, and MnCl2·4H2O is replaced by ferric chloride with the same doping ratio (2%). The rest is the same as Example 1, and a light-converting packaging film is obtained.

[0088] Example 5

[0089] The difference from Example 1 is that the temperature parameters for preparing the light conversion packaging film in step S2 are set differently.

[0090] Step S1: same as in Example 1;

[0091] Step S2: preparing light-converting packaging film:

[0092] Heat the pelletizing extruder to 210°C in the middle module and 180°C at both end modules, add polypropylene pellets for flushing until the extruded strips are transparent;

[0093] Take 20g CsCdCl3:2%Mn, grind it to 10-30μm, add 1kg polypropylene particles, 5mL white oil, and 10g PBAT dispersant in sequence, stir thoroughly, add it to the granulation extruder, and cut the extruded strips into particles; add the above particles to a tablet press at 180°C and extrude it. The extrusion thickness of the tablet press is adjusted to 50μm to obtain a light-converting encapsulation film.

[0094] Comparative Example 1

[0095] Different from Example 1, in step S1, metal Mn is not doped and only CsCdCl3 is prepared.

[0096] Step S2 is the same as in Example 1.

[0097] The light-converting packaging film product obtained in Comparative Example 1 has a low luminous efficiency of CsCdCl3 without metal Mn doping, which easily leads to errors in testing, and the photoluminescence quantum yield is 2.3%.

[0098] Comparative Example 2

[0099] The difference from Example 1 is that the metal X in step S1 is Pb, and MnCl2·4H2O is replaced by lead stearate with the same doping ratio (2%). The rest is the same as Example 1, and a light-converting packaging film is obtained.

[0100] Comparative Example 3

[0101] The difference from Example 1 is that the doping ratio of Mn in step S1 is 20%. The rest is the same as Example 1, and a light-converting packaging film is obtained.

[0102] Comparative Example 4

[0103] The difference from Example 1 is that the insulation temperature in step S1 is different, specifically:

[0104] S1. Preparation of CsCdCl3:2%Mn by hydrothermal method:

[0105] According to the stoichiometric ratio of 2% Mn doping, MnCl2·4H2O (0.1878 g) and CdCl2 (0.3797 g) were weighed and added into a 100 mL polytetrafluoroethylene reactor; 70 mL of HCl (36%) solution was added into the polytetrafluoroethylene reactor and shaken vigorously for 2 min until the powder was completely dissolved;

[0106] Weigh CsCl (3.367 g) and add it to the above polytetrafluoroethylene reactor. A white precipitate will be generated immediately. Shake vigorously for 2 min. Then keep it at 65 °C for 5 h.

[0107] After the reaction was completed, the white precipitate sample was washed with deionized water and ethanol in turn; the obtained sample was dried at 65°C for 12h to obtain CsCdCl3:2%Mn;

[0108] Step S2: Same as Example 1.

[0109] Comparative Example 5

[0110] The difference from Example 1 is that the temperature of step S2 is different, specifically:

[0111] Step S1: same as in Example 1;

[0112] Step S2: preparing light-converting packaging film:

[0113] Heat the pelletizing extruder to 120°C in the middle module and 110°C at both ends, add polypropylene pellets for flushing until the extruded strips are transparent;

[0114] Take 20g CsCdCl3:2%Mn, grind it to 10-30μm, add 1kg polypropylene particles, 5mL white oil, and 10g PBAT dispersant in sequence, stir thoroughly, add it to the granulation extruder, and cut the extruded strips into particles; add the above particles to a tablet press at 120°C and extrude it. The extrusion thickness of the tablet press is adjusted to 50μm to obtain a light-converting encapsulation film.

[0115] Comparative Example 6

[0116] The photoconversion layer was prepared according to the method described in Example 1 of patent CN117887377A, and the thickness of the photoconversion layer was 200 μm.

[0117] The raw materials of the transfer layer include the following components by weight: 100 parts of EVA resin, Eu 3+ 0.3 parts of modified organic photoconverter powder, 1 part of silane coupling agent, 0.5 parts of crosslinking agent, 0.5 parts of auxiliary crosslinking agent, 0.5 parts of acrylic monomer, 0.05 parts of light stabilizer and 0.05 parts of antioxidant; the silane coupling agent is vinyl triethoxysilane, the crosslinking agent is tert-amyl peroxy (2-ethylhexyl) carbonate, the auxiliary crosslinking agent is triallyl isocyanurate, the antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and the light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.

[0118] Eu 3+ The preparation method of the modified organic light-converting powder comprises:

[0119] (a) Weigh 2g acrylamide, 0.1g CdSO4·8 / 3H2O and 0.08g ammonium persulfate and dissolve them in 8g deionized water, stir until dissolved to prepare the aqueous phase; weigh 1.6g Span 80 and dissolve it in 40g cyclohexane, stir magnetically for 10min to prepare the oil phase. Pour the aqueous phase into the oil phase and pre-emulsify it with magnetic stirring for 15min. Ultrasonicate the pre-emulsion for 5min, pour it into a four-necked flask, turn on the stirrer, and react in a water bath at 65℃ for 4h under N2 protection to obtain a CdSO4-PAM emulsion;

[0120] (b) weighing 0.094 g of Na2S·9H2O and 0.3 g of acrylamide and dissolving them in 2 g of deionized water and stirring until dissolved to obtain a Na2S aqueous solution;

[0121] (c) Na2S aqueous solution was added dropwise to CdSO4-PAM emulsion at a constant rate of 10 mL / h through a micro-injection pump, and then kept warm and sealed at 65°C for 3 h with stirring; 30 g of EuCl3·6H2O was weighed and dissolved in 300 g of deionized water to obtain EuCl3·6H2O aqueous solution; EEuCl3·6H2O aqueous solution was then added dropwise at a constant rate of 100 mL / h through a micro-injection pump, and kept warm and sealed at 65°C for 2 h with stirring to obtain Eu 3+ Doped CdS-PAM composite emulsion;

[0122] (d) Measure the Eu obtained in step (c) 3+ The doped CdS-PAM composite emulsion was poured into a hydrothermal reactor lined with polytetrafluoroethylene, placed in a constant temperature blast drying oven, reacted at 100°C for 6 hours, and centrifuged. The resulting precipitate was washed twice with anhydrous ethanol and then placed in a 50°C vacuum drying oven for 10 hours to obtain Eu 3+ Doped CdS quantum dot powder;

[0123] (e) Weigh 100 parts by weight of benzotriazole photoconversion powder, 5 parts by weight of UV-329, and 5 parts by weight of Eu 3+ Doped CdS quantum dot powder was added to 10 mL of ethyl acetate and mixed evenly; then 5 parts by weight of tetraethyl orthosilicate, 3 parts by weight of 3-methacryloxypropyltrimethoxysilane and 0.5 parts by weight of a water / ethanol mixture (the volume ratio of ethanol to water was 1:1) were added, ultrasonicated at room temperature for 30 min, and the solvent was removed by rotary evaporation at 65 ° C and dried to obtain Eu 3+ Modified organic photoconverter powder.

[0124] The preparation method of light-converting packaging film is as follows: the temperature of each zone of the single-screw extruder is set as follows: 65°C in zone I, 75°C in zone II, 80°C in zone III, 80°C in zone IV, 80°C in zone V, 85°C in zone VI, 85°C in zone VII, 85°C in zone VIII, 85°C in zone IX, and 90°C in the die zone; three die heads ABC are co-extruded, stretched, pulled, and rolled by melting, and the total thickness of the packaging film is 0.5 mm; then, the electron beam irradiation parameters are as follows: voltage 0.5MV, beam current 30mA, and line speed 30M / min to obtain the light-converting packaging film.

[0125] 1. Excitation, emission spectrum and UV absorption test

[0126] Experimental method: Take the product (cesium-based metal halide, CsCdCl3 powder) obtained in step S1 of each embodiment and comparative example and add it to the photoluminescence test solid stage, set the excitation light source to 254nm, and collect data after the test is completed.

[0127] The products (cesium-based metal halide, CsCdCl3 powder) obtained in step S1 of each embodiment and comparative example were subjected to excitation, emission spectrum and ultraviolet absorption tests. The emission spectrum shows that the CsCdCl3:2%Mn of Example 1 can be effectively excited by ultraviolet light at 220-400nm ( Figure 2 ), the CsCdCl3 of comparative example 1 has an emission spectrum range of 500-700nm under the excitation of ultraviolet light with a wavelength of 254nm, and the main emission peak is located at 590nm ( Figure 1 ); The CsCdCl3:2%Mn material of Example 1 has an emission spectrum range of 500-700nm under the excitation of ultraviolet light with a wavelength of 254nm, and the main emission peak is located at 604nm ( Figure 2 ).

[0128] like Figure 3 As shown, the CsCdCl3:2%Mn prepared in Example 1 and the CsCdCl3 sample prepared in Comparative Example 1 both have an absorption peak at 360-366nm, while the CsCdCl3:2%Mn in Example 1 has an additional small absorption peak at 420nm.

[0129] 2. XRD test

[0130] Experimental method: Take the product (cesium-based metal halide, or CsCdCl3 powder) obtained in step S1 of each embodiment and comparative example, add it to the XRD test solid table, flatten it, put it into the machine, and set the scanning angle to 5-50°. Collect data after the test is completed.

[0131] Figure 4 are X-ray diffraction patterns of Example 1 CsCdCl3:2%Mn and Comparative Example 1 CsCdCl3; Figure 4 From top to bottom are the XRD data of CsCdCl3:2%Mn and the XRD data of CsCdCl3. Figure 4 The XRD results show that the prepared cesium-based halide crystals maintain the same crystal structure while Mn 2+ After successfully entering the matrix lattice, the Bragg diffraction peak shifts slightly to a higher 2θ angle.

[0132] 3. Emission spectrum, fluorescence quantum yield and UV absorption test

[0133] Emission spectrum: Take 500 mg of the product powder of step S1 and add it to the luminescence test solid platform, set the excitation light source to 604 nm, and collect data after the test is completed.

[0134] Fluorescence quantum yield: 500 mg of the product powder from step S1 was placed on a solid glass stage, the excitation light source was set to 300 nm, and data was collected after the test was completed.

[0135] UV absorption test: 200 mg of the product powder from step S1 was added to the test solid platform, and the scanning range was 300-800 nm. Data was collected after the test was completed.

[0136] The emission spectrum, fluorescence quantum yield and UV absorption of the light-converting packaging film were tested. Figure 5 : This is the emission spectrum of the light-converting packaging film of Example 1. When the 50 μm light-converting packaging film is exposed to 254 nm ultraviolet light, the emission peaks of the two samples are substantially around 604 nm.

[0137] Figure 6 This is the ultraviolet absorption spectrum of the light-converting packaging film prepared in Example 1.

[0138] Figure 7 This is a test diagram of the fluorescence quantum yield of the light-converting encapsulating film prepared in Example 1. The quantum yield of the light-converting encapsulating film is 81.5% (50 μm). Figure 7 The reference in the figure is the transparent optical quartz carrier glass in which the sample is loaded.

[0139] 4. Water stability test

[0140] Experimental method: Take a 1cm piece of light-converting packaging film and put it into a sealed container filled with water, and test its luminous intensity at different times.

[0141] from Figure 8 It can be seen from the water stability test results that after being immersed in water for 30 days, the fluorescence intensity of the light conversion packaging film of Example 1 can still maintain 80.6% of the initial value. Figure 8 The lines from top to bottom at 604 nm are the fluorescence intensity data of the 1st day, the 5th day, the 10th day, the 15th day, the 20th day, and the 30th day, respectively.

[0142] 5. SEM and EDS testing

[0143] Experimental method: Take a 1cm piece of light-converting packaging film and place it on the SEM stage for direct observation.

[0144] The light conversion packaging film prepared in Example 1 was tested by SEM and EDS. Fig. 9 The surface scanning electron microscope images of the light-converting packaging film of Example 1 at 200 μm (left picture) and 20 μm (right picture) magnification conditions show that the cesium halide is uniformly mixed in the polypropylene.

[0145] Fig.10This is a test diagram of the surface element distribution of the light-converting packaging film of Example 1. It can be seen that the three elements Cs, Cd, and Mn are evenly distributed in the polymer, among which the Cs element accounts for 26.94wt%, the Cd element accounts for 32.5wt%, the Mn element accounts for 3.75wt%, and the remaining element is Cl.

[0146] 6. AFM test

[0147] Experimental method: Take a 1 cm piece of the prepared light-converting packaging film and place it on the AFM stage for direct observation.

[0148] The light-converting packaging film prepared in Example 1 was subjected to AFM test. Fig.11 As shown, the profile of the light-converting packaging film prepared in Example 1 (50 μm) has an arithmetic mean deviation Ra of 41.7 nm.

[0149] Fig.12 The photo of the light-converting packaging film prepared in Example 1 is shown under a fluorescent lamp (left picture) and under 300nm ultraviolet irradiation (right picture).

[0150] The cesium-based metal halides of Examples 1 to 4, Comparative Examples 2 to 5, CsCdCl3 of Comparative Example 1, and Eu of Comparative Example 6 3+ The absorption peak wavelength, photoluminescence range, luminescence peak and photoluminescence quantum yield of the modified organic photoconversion powder are shown in Table 1.

[0151] Table 1

[0152]

[0153] As can be seen from Table 1, the CsCdCl3:2%Mn composite light-conversion encapsulation film has higher pl intensity (photoluminescence intensity) and photoluminescence quantum yield than other systems; the present invention achieves light wavelength conversion by doping a small amount of Mn, converting the light wavelengths (ultraviolet and blue light) that the solar cell cannot effectively utilize into wavelengths (near infrared light) that the cell can absorb, so as to enhance the luminous efficiency and power generation efficiency of the solar cell. And the CsCdCl3:2%Mn composite light-conversion encapsulation film of the present invention will not block the solar cell from absorbing other wavelengths of light.

[0154] The water stability technical effects of the light conversion packaging films of Example 1, Example 3, Comparative Example 1, Comparative Example 3, and Comparative Example 5 are shown in Table 2:

[0155] Table 2

[0156]

[0157] It can be seen from Table 2 that the CsCdCl3:2%Mn composite light-converting encapsulation film has higher water stability than other systems.

[0158] In summary, the cesium-based metal halide composite light-conversion packaging film prepared by the present invention can improve the light absorption efficiency of solar cells, extend the service life of solar cell modules, improve the conversion rate of the light-conversion packaging film to ultraviolet light, improve the power generation efficiency of photovoltaic modules, and reduce the attenuation of power generation efficiency after module aging; the preparation process of the present invention is simple and environmentally friendly, and is compatible with existing photovoltaic production processes.

[0159] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a cesium-based metal halide composite light-conversion packaging film, characterized in that: Includes steps: S1. Prepare cesium-based metal halide by hydrothermal method: dissolve cadmium chloride and chloride of metal X in hydrochloric acid solution to obtain mixture A; mix mixture A with cesium chloride and keep warm to obtain Cs(Cd-X)Cl3; The metal X is selected from at least one of Mn, Sb, Eu, and Fe; the doping ratio of the metal X is 0.1-15%; The mixing and heat preservation in step S1 is as follows: heat preservation at 150-170°C for 8-16 hours, then cool to room temperature at a rate of 0.3-1°C / min, and store at room temperature for 36-54 hours; S2, preparing a light-converting encapsulating film: Cs(Cd-X)Cl3 is mixed with a polymer material, white oil and a PBAT dispersant, and processed by a granulating extruder and a tablet press to obtain a light-converting encapsulating film with a thickness of 50-110 μm; In step S2, the parameters of the granulation extruder are: 210-240°C for the middle module and 180-200°C for the two end modules; the working temperature of the tablet press is 180-240°C.

2. The preparation method according to claim 1, characterized in that: In step S1, the doping ratio of the metal X is 1-5%; the mass concentration of the hydrochloric acid solution is 30-40wt%; the mass ratio of cadmium chloride to cesium chloride is 1:7-10; and the mass volume ratio of cesium chloride to hydrochloric acid solution is 2.5-4:70g / mL.

3. The preparation method according to claim 2, characterized in that: In step S1, the doping ratio of the metal X is 2%; the mass concentration of the hydrochloric acid solution is 36wt%; and the mass ratio of cadmium chloride to cesium chloride is 1:8-9.

4. The preparation method according to claim 1, characterized in that: Step S1 further includes washing and drying steps after mixing and heat preservation.

5. The preparation method according to claim 4, characterized in that: In step S1, the mixed heat preservation is: heat preservation at 160°C for 12 hours, then cool to room temperature at a rate of 0.5°C / min, and store at room temperature for 48 hours.

6. The preparation method according to claim 1, characterized in that: In step S2, the polymer material is selected from at least one of polypropylene, polycarbonate, polymethyl methacrylate, polyvinylidene fluoride, ethylene-vinyl alcohol copolymer, acrylonitrile-butadiene-styrene copolymer, polyvinylidene chloride, polyethylene terephthalate, and polyethylene terephthalate; The white oil is mineral oil; The PBAT dispersant is polybutylene terephthalate-adipate.

7. The preparation method according to claim 1, characterized in that: In step S2, the extrusion thickness of the tablet press is 50-60 μm or 100-110 μm; In step S2, the mass ratio of the Cs(Cd-X)Cl3, polymer material and PBAT dispersant is 1-3:50-150:0.5-2; the mass volume ratio of Cs(Cd-X)Cl3 to white oil is 20:3-8 g / mL.

8. A light-converting packaging film, prepared by the preparation method according to any one of claims 1 to 7; the light-converting packaging film comprises components: Cs(Cd-X)Cl3, polymer material, white oil and PBAT dispersant; The mass ratio of Cs(Cd-X)Cl3, polymer material and PBAT dispersant is 1-3:50-150:0.5-2; the mass volume ratio of Cs(Cd-X)Cl3 and white oil is 20:3-8g / mL; X is at least one selected from the group consisting of Mn, Sb, Eu, and Fe.

9. A cesium-based metal halide prepared by the preparation method according to any one of claims 1 to 7, comprising CsCdCl3 and metal X, wherein the metal X is selected from at least one of Mn, Sb, Eu, and Fe.

10. Use of the cesium-based metal halide according to claim 9 in the preparation of a light-converting packaging film.

Citation Information

Patent Citations

  • Preparation method and application of perovskite quantum dot light conversion adhesive film

    CN116970346A

  • High-reflection packaging adhesive film for main-grid-free battery assembly, preparation method of high-reflection packaging adhesive film and photovoltaic assembly

    CN117887377A

  • Upconversion phosphor materials as well as preparation method and application thereof

    CN107974251A

  • Manganese-doped cesium-lead-chlorine illuminant based on silicon dioxide coating and preparation method and application thereof

    CN113025311A